Firmware development and testing of the ATLAS Pixel Detector / IBL ROD card - Gabrielli, Alessandro; Kretz, Moritz; Kugel, Andreas (Journal of Instrumentation, 2015)
The ATLAS Experiment is reworking and upgrading systems during the current LHC shut down. In particular, the Pixel detector has inserted an additional inner layer called the Insertable B-Layer (IBL). The Readout-Driver card (ROD), the Back-of-Crate card (BOC), and the S-Link together form the essential frontend data path of the IBL's off-detector DAQ system. The strategy for IBL ROD firmware development was three-fold: keeping as much of the Pixel ROD datapath firmware logic as possible, employing a complete new scheme of steering and calibration firmware, and designing the overall system to prepare for a future unified code version integrating IBL and Pixel layers. Essential features such as data formatting, frontend-specific error handling, and calibration are added to the ROD data path. An IBL DAQ test bench using a realistic front-end chip model was created to serve as an initial framework for full offline electronic system simulation. In this document, major firmware achievements concerning the IBL ROD data path implementation, test on the test bench and ROD prototypes, will be reported. Recent Pixel collaboration efforts focus on finalizing hardware and firmware tests for the IBL. The plan is to approach a complete IBL DAQ hardware-software installation by the end of 2014.